Assessment of Yield Gaps in Chickpea Production in Shimla District of Himachal Pradesh - Kumari, Neelam; Thakur, Ashok K.; Kaith, N. S. (International Journal of Economic Plants, 2019)
Though substantial progress has been made in evolving techniques to obtain high yields of pulses, however, their productivity has remained lower than the potential yields for the last few decades. Acreage and productivity of pulse crop is declining in Himachal Pradesh and Shimla district as well. To boost the production and productivity of pulse crops, Krishi Vigyan Kendra Shimla is conducting cluster frontline demonstrations (CFLD) on pulse crops. The main objective of CFLD on pulses is to demonstrate and popularize the improved technologies on farmers’ fields for effective transfer of generated technology and fill the gap between recommended practices and farmers’ practices and ultimately to boost the production of pulses. Frontline demonstrations in chickpea during rabi season were studied for four years (Rabi 2015-16, Rabi 2016-17, Rabi 2017-18 and Rabi 2018-19) in Shimla district of Himachal Pradesh. There was a wide yield gap between the potential and demonstration yields mainly due to technology and extension gaps. CFLD on chickpea crop indicated that increase in yield over farmers’ practice ranged from 22.22 to 68.44% over four years. In terms of economics, chickpea crop recorded higher net returns hectare-1 compared to farmer’s practice during all the years. The benefit:cost ratio of demonstration plots ranged from 1.21 to 2.63. The technology index varied from 10.29 to 45.00% indicating the urgent need to motivate the farmers to adopt economical viable technologies for increasing production, productivity and profitability of chickpea.